Significance of Taguchi Design compared to Response Surface Methodology in predicting optimal machining conditions for PCM process. Issue 1 (April 2021) - Uday Kiran, K A V; Vigneshwar, N; Solomon, Darius Gnanaraj; Arulraj, Joseph Jeyapaul
Abstract: Photochemical Machining (PCM) is a non-conventional machining process which produces stress free complex flat metal components. Optimization of process parameters for Photochemical machining of SS316L steel is done using Taguchi method and the results are compared with results obtained through Response surface methodology (RSM) available in literature. The objective of this work is to predict the optimal machining conditions of PCM to achieve minimum undercut for SS316L steel. The Factors affecting the response of the model are: Etching Time (Ti), Temperature (T) and Etchant Concentration (C) in PCM. This work shows that Taguchi method is faster compared to RSM in predicting the optimal conditions for minimizing defects in PCM process. Taguchi method requires only 9 experiments for finding optimal conditions whereas RSM requires 20 experiments saving about 55% of time and effort.